Comparison of students’ metacognitive skills by gender on chemical bonding in chemistry - Naseer Ahmed; Naseer Ahmed; Antuni Wiyarsi; Rar.Nat. Senam (JURNAL PENDIDIKAN SAINS (JPS), 2019)
The main purpose of this research is to investigate the metacognitive skills of students from class 10th in Bantul and to analyze the comparison between them based on their gender. The method of this research is quantitative descriptive. A questionnaire was used to collect data. The questionnaire was applied in four classes in order to collect data and independent T-test was used to analyze them, the findings proved that generally both male and female use their metacognitive skills in learning. In addition, there are no significant differences between male and female students in metacognitive skills especially in the following domains: knowledge about cognition. The results are discussed in relation and compared with previous researches to show gender differences in chemistry learning and opens the door for future research and educational practice. It is recommended to conduct further research related to gender differences in metacognitive skills using a bigger sample.